The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fimmu.2018.00148
|View full text |Cite
|
Sign up to set email alerts
|

Interorgan Molecular Communication Strategies of “Local” and “Systemic” Innate Immune Responses in Mosquito Anopheles stephensi

Abstract: Mosquitoes that transmit many deadly infectious diseases also need to keep fighting against many microbial infections. Constitutive expression of multiple antimicrobial peptides (AMPs) in almost all body tissues is believed to facilitate the effective management of these local infections. When any infection breaches the local barrier, AMPs are induced rapidly in non-target tissues such as hemocytes (HCs) and establish their co-ordination with systemic immune effectors to clear off the body infection. But how i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 63 publications
4
32
0
Order By: Relevance
“…Thus, we hypothesize first 24 hrs of gut-microbe-Plasmodium interaction in the gut lumen are crucial for Plasmodium survival, where it may limit the availability of iron/nutrient required for bacterial growth (Clark, Goheen et al 2014). Corroborating to earlier studies, we also observed that mosquitoes were able to restore basal level of gut flora within 30hrs of uninfected blood meal digestion (Das De et al, 2018). However, surprisingly, P. vivax infection caused a major shift in gut flora restoration to an enriched state after 48 hrs in P. vivax infection.…”
Section: Fig 8 Relative Quantification Of Gut Immune Transcripts Insupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, we hypothesize first 24 hrs of gut-microbe-Plasmodium interaction in the gut lumen are crucial for Plasmodium survival, where it may limit the availability of iron/nutrient required for bacterial growth (Clark, Goheen et al 2014). Corroborating to earlier studies, we also observed that mosquitoes were able to restore basal level of gut flora within 30hrs of uninfected blood meal digestion (Das De et al, 2018). However, surprisingly, P. vivax infection caused a major shift in gut flora restoration to an enriched state after 48 hrs in P. vivax infection.…”
Section: Fig 8 Relative Quantification Of Gut Immune Transcripts Insupporting
confidence: 84%
“…A constant 28±2°C temperature and relative humidity of ~80% was maintained in the insectarium. Live rabbit was offered for blood meal for egg maturation and gonotrophic cycle maintenance (Sharma et al 2015;Das De, Sharma et al 2018).…”
Section: Materials and Methods: Technical Overview Presented In Supplementioning
confidence: 99%
“…Briefly, post confirmation of P. vivax infection, ~20-25 mosquitoes were dissected at 3-6Days Post Infection (DPI) and 8-10 DPI for midgut, 9-12DPI for hemocytes and 12-14DPI for salivary glands in PBS and collected in trizol reagent. Total RNA was isolated from each dissected tissue sample, and respective double stranded cDNA library was prepared using well established protocol, described earlier (De et al, 2018;Dixit et al, 2011;Sharma et al, 2015). The sequencing of whole transcriptomes was performed on Illumina NextSeq.…”
Section: Methodsmentioning
confidence: 99%
“…Our initial attempt of mapping of cleaned reads (filtered low quality, microbial and P. vivax origin) to the available draft reference genome was unsuccessful. Alternatively, we mapped all the high quality reads against denovo assembled reference map, as described earlier (De et al, 2018;Sharma et al, 2015;. Though, a read density map analysis revealed P. vivax infection causes a significant suppression in the salivary glands and midgut transcripts, but cause a greater shift in the read density of the infected hemocyte transcripts (Fig.2).…”
Section: Working Hypothesis Development and Rnaseq Data Generationmentioning
confidence: 97%
See 1 more Smart Citation